Facilitating Expatriates Cross Cultural Adjustment (A Case study of Expatriates from Pakistani Organization on Foreign - Ghafoor, Shahzad; Khan, Uzair Farooq (Journal of Asian Scientific Research, 2011)
The purpose of this study is to illustrate the importance of expatriates (employees) from Pakistani organizations on foreign assignment by critically analyzing the significance of their strategic roles. Then it reveals that why expatriates fail and effect of cultural distance on them. Finally, what MNE’s and Institutions can do for facilitating their successful adjustment? The significance of Management in the organization is inevitable after the emergence of the new concept of the “Amalgamation”. A detail study was conducted to observe the prevailing Knowledge Management practices and constraints related to it in the selected organization of Pakistan Habib Rafiq Limited (HRL). A case study methodology was adopted for the research purpose. On the basis of the developed conceptual frame work observation was made and interviews were conducted to find out the current knowledge management practices at Habib Rafiq Limited (HRL) Lahore. After data analysis a model was developed for facilitating cross cultural adjustment. It is suggested that if implemented this model can help the organizations and Institutions in improving its current status. This study provided strong evidence to suggest that there should be further research in this field.